Seepage handling using secant pile as a solution to replace curtain grouting and dam stability evaluation to optimize work on the Margatiga Dam construction project - Ahmad Sidik (Jurnal Indonesia Sosial Teknologi, 2024)
Based on the results of a soil investigation using the bore log method carried out by the Consultant, it was found that the foundations of the spillway building and intake building are in a geological condition that is composed predominantly of sand and porous deposits or easily absorbs water, as well as rocks with the characteristics of fine tuff rock, indicating that the foundation The building is prone to seepage. The seepage treatment contained in the contract is the curtain grouting method 20 meters deep with a distance of 2 meters between points. It is necessary to carry out trial grouting in 3 location zones to be sure. Therefore, it is necessary to analyze the secant pile design. In the work on filling the dam body on the left and right sides, a review needs to be carried out to optimize the implementation of the work because it has a safety factor that is too high than the required safety factor. Secant pile design planning and cross-section evaluation calculations use software to help calculate seepage and stability analysis. Based on the results of modeling analysis calculations and evaluation of cost and implementation time calculations that meet the criteria, it is recommended to handle seepage using secant piles, namely with dimensions of 80 cm, overlap of 15 cm and a depth of up to -10 elevation and recommendations for the cross-section of the dam body, namely by modifying the slope of the section.